Ionic Channels as Potential Therapeutic Targets for Erectile Dysfunction: A Review - Diniz, Anderson Fellyp Avelino; Ferreira, Rafael Carlos; de Souza, Iara Leão Luna; da Silva, Bagnólia Araújo (Frontiers in Pharmacology, 2020)
Erectile dysfunction (ED) is a prevalent condition, especially in men over 40 years old, characterized by the inability to obtain and/or maintain penile erection sufficient for satisfactory sexual intercourse. Several psychological and/or organic factors are involved in the etiopathogenesis of ED. In this context, we gathered evidence of the involvement of Large-conductance, Ca2+-activated K+ channels (BKCa), Small-conductance, Ca2+-activated K+ channels (SKCa), KCNQ-encoded voltage-dependent channels K+ (KV7), Transient Receptor Potential (TRP) channels, and Calcium-activated Chloride channels (CaCC) dysfunctions on ED. In addition, the use of modulating agents of these channels are involved in relaxation of the cavernous smooth muscle cell and, consequent penile erection, suggesting that these channels are promising therapeutic targets for the treatment of erectile dysfunction.